Group Counseling with Sociodrama for Improving Student's Prosocial Behavior - Kusumaningrum, Intan; Purwanto, Edy; Sugiyo, Sugiyo (Jurnal Bimbingan Konseling)
The present study was aimed at finding out the effectiveness of group guidance with sociodrama for improving student's prosocial behavior. This study employed experimental method with one group pretest Posttest design, involving ten students as the members of the group. The analysis result using Wilcoxon test showed that group guidance with sociodrama technique was effective to improve student?s prosocial behavior. The result of the study showed that group guidance in SMP Negeri Kabupaten Pemalang had been planned within guidance and counseling program. However, its implementation was sub-optimal. The present study also found that group guidance with sociodrama is effective for improving student?s prosocial behavior. The discussion of the result of the study is aimed at identifying the implication of group guidance with sociodrama in improving student?s prosocial behavior.